Evolutionary parasitology the integrated study of infections, immunology, ecology, and genetics - Schmid-Hempel, Paul (Oxford University Press, 2021)
Concepts from evolution, ecology, parasitology, and immunology have informed a new synthesis of host-parasite interactions. The book builds on these established approaches whilst including some of the most successful interdisciplinary areas of modern biology - evolutionary epidemiology and ecological immunology.